Marie Ruel, "Global Survey of School Meal Programs: Implications & Perspectives" - Ruel, Marie T. (2019)
Marie Ruel SPECIAL EVENT Global Survey of School Meal Programs: Implications & Perspectives Co-Organized by Global Child Nutrition Foundation (GCNF) and IFPRI APR 10, 2019 - 09:00 AM TO 12:30 PM EDT